Hubungan Status Gizi dan Durasi Tidur dengan Siklus Menstruasi pada Remaja Putri di MA Al-Mumtaz - Anggoro, Sarni; Isnaningsih, Tantiana; Kurnia Sari, Chanif; Agustina Rahayu, Bety; Khamid, Ahmad (Universitas Widya Mataram, 2025)
Female teenagers usually experience disorders such as menstrual pain that makes them reluctant to eat, thus affecting their nutritional status, and menstrual pain can also disrupt sleep duration. This study aims to determine the relationship between nutritional status and sleep duration with the menstrual cycle of female adolescents at MA Al Mumtaz. This approach uses a Cross sectional approach. The total population is 46 students. Based on the results of the study, it shows that the majority of respondents aged 17 years (28.1%) have a good nutritional status (75%). The majority of them have a sleep duration in the poor category (68.8%) and an irregular menstrual cycle (59.4%). The majority of respondents have an irregular menstrual cycle with a sleep duration that is in the poor category. The results of the Analysis test showed that there was a relationship between the menstrual cycle and sleep duration (p-value = 0.025). The majority of those with irregular menstrual cycles had good nutritional status. The results of the Analysis test showed that there was also a relationship between the menstrual cycle and nutritional status (p-value = 0.008).